Sosialisi Ekonomi Syariah di Sekolah Dasar Sakinah - Zulkifli, Zulkifli; Hermanto, Budi; Eka Saputra, Hendra; Zaky Pratama, Daffa; Vanisa, Nia (Al-ihsan: Jurnal Pengabdian Agama Islam, 2025)
This Community Service (PKM) activity was conducted at Sakinah Elementary School in Pandau Village, Siak Hulu District, Kampar Regency, with the aim of improving teachers' literacy and understanding of Islamic economic principles. The main problem faced by the partners was teachers' lack of understanding of the basic concepts of Islamic economics and their application in daily life and in the learning process. The activity was implemented through several stages: outreach, training, mentoring, and a workshop on the application of Islamic economics in the school environment. The results showed a 75% increase in teachers' understanding of Islamic economic concepts after participating in the training. Furthermore, three subjects were successfully integrated with Islamic economic values, and a Sharia-based mini-cooperative was established as a result of the direct application of Islamic principles in schools. Sharia economic learning modules and a simple financial recording application were also developed to support the program's sustainability. This activity had a positive impact on improving teacher competency, students' Islamic financial literacy, and the application of Islamic values ​​in economic activities and basic education